2019
DOI: 10.3892/etm.2019.7857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features in toxic coma in children

Abstract: The purpose was to identify rapidly the etiology of toxic coma in children, to appreciate the severity of the coma, to detect elements of gravity based on associated clinical signs and symptoms and to evaluate the initial treatment. Toxic coma is a medical emergency, especially in a Pediatric Emergency Department, requiring rapid and precise evaluation. The key objectives in the evaluation and management of coma in children are: detecting severity characteristics, depth of coma, specific clinical signs and sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…As regard Reed scale, the present results are in harmony with Stanca et al (8) results as they concluded that the increase of the degree of Reed scale were associated with bad prognosis. Convulsions, disturbance of heart beats and respiratory distress syndrome were more severe and frequent with 4 th degree Reed scale than the other lower degrees.…”
Section: Discussionsupporting
confidence: 91%
“…As regard Reed scale, the present results are in harmony with Stanca et al (8) results as they concluded that the increase of the degree of Reed scale were associated with bad prognosis. Convulsions, disturbance of heart beats and respiratory distress syndrome were more severe and frequent with 4 th degree Reed scale than the other lower degrees.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with grade III had impaired reflexes. Patients in the grade IV toxic coma were unstable with affected vital center functions (Stanca et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the autoimmune nature of uveitis, patients should be tested for associated diseases before administering intraocular steroids (8)(9)(10)(11)(12). In order to exclude an infectious cause of uveitis, general examination and blood tests should be performed (13)(14)(15)(16)(17)(18). Triamcinolone acetonide (TA) belongs to the glucocorticoid family.…”
Section: Triamcinolone Acetonide Induces Sterile Endophthalmitis In Pmentioning
confidence: 99%